Overcoming barriers to social media use through multisensor integration in emergency management systems. (December 2021) - Grace, Rob
Abstract: For over a decade, the field of crisis informatics has observed novel, ad hoc uses of social media among citizens and digital volunteers while noting barriers that impede social media use among municipal responders during crises. These barriers include a lack of tools for processing social media data, a lack of staff to use these tools, and a lack of trust in information gathered from citizens. However, while studies address the collection, processing, and use of social media per se, research continues to overlook the necessity of integrating information gathered from social media and existing information sources relied on by responders working across municipal agencies. Through scenario-based interviews with municipal responders, this study observes that objectives of early warning and proactive emergency response motivate uses of social media during periods of stability to address gaps in information reported by 911 callers, on-scene responders, and various physical sensors. To accomplish these objectives, upstream PSAP staff must process information from multiple physical and social sensors, cue other sensors to verify untrusted reports, and integrate multisensor information for dispatch to downstream first responders, emergency managers, and PIOs. Together, these findings suggest that overcoming barriers to social media use resulting from a lack of tools, staff, and trust requires new and existing sociotechnical infrastructures that facilitate intra- and inter-organizational processes of multisensor integration across periods of stability and crisis.